A case study of a production unit in an electronic firm / Phang Kim Seong - Phang , Kim Seong (1977)
The report serves to present a study of the performance of a line of production system in an electronic firm. Due to the practice of decentralization of management, the production unit has the unique feature that it operates like a separate body. The general belief is that this will serve as a means for encouraging commitment from an individual to achieve an expected accomplishment by making him answerable for the accomplishment and by giving him personal recognition. The line produces various types of Light Emitting Diode, each with different specifications as designed by customers who make their orders to the marketing department of this particular organisation in U.S.A. A standard cost, as fixed by the marketing department, is provided for each individual product, hence forms a guide to the manufacturing cost. Profit and loss of the line are calculated based on the comparison of the actual manufacturing cost with the standard cost. Judging from the fact that the line was able to produce a negative variance (profit) of US$ 30,000 last year clearly indicates that the operation of the line had been efficient.